إدارة الذات وعلاقتها بالكفاءة المهنية لدى معلمات رياض الأطفال - الخطيب، ندي ناصر محمد مصطفي Alkhatib, Nada Nasser Mohammed Mustafa; مالك، خالد مصطفى محمد; عبدالحميد، عزة خضري (جامعة حلوان - كلية التربية, 2021)
نتيجة لما شهده العالم في السنوات الأخيرة من تطورا معرفيا وتحديات هائلة كان له أكبر الأثر على العملية التعليمية، ولما كان اتجاه الكفايات التعليمية يعد من أبرز الاتجاهات الحديثة التي سادت برامج إعداد المعلمين عامة ومعلمات رياض الأطفال بوجه خاص وتدريبهم خلال العقود الثلاثة الماضية وقد تفاقم وتعاظم دور هذا الاتجاه خاصة مع تطبيق الجودة الشاملة وزيادة التنافسية بين المؤسسات التعليمية للحصول على الاعتماد الأكاديمي. أهداف الدراسة: 1. الكشف عن العلاقة بين متوسطات درجات إدارة الذات والكفاءة المهنية لدى معلمات رياض الأطفال. 2. الكشف عن الفروق بين متوسطات درجات معلمات رياض الأطفال على مقياس إدارة الذات والذي يعزى إلى نوع التعليم (خاص/ حكومي). 3. الكشف عن الفروق بين متوسطات درجات معلمات رياض الأطفال على مقياس الكفاءة المهنية والذي يعزى إلى نوع التعليم (خاص/ حكومي). عينة الدراسة: - تكونت عينة الدراسة من عدد (110) من معلمات رياض الأطفال الحاصلات على مؤهل عال في مجال التخصص "رياض الأطفال"، وممارسات للمهنة في المدارس الحكومية والخاصة والتجريبي والإنترناشونال. منهج الدراسة: - استخدمت الباحثة المنهج الوصفي الارتباطي وذلك لطبيعة الدراسة وأهدافها. نتائج الدراسة: - 1. توجد علاقة ارتباطية موجبة دالة إحصائيا بين درجات أفراد عينة البحث على مقياس إدارة الذات ودرجاتهم على مقياس الكفاءة المهنية. 2. لا يوجد فرق دال إحصائيا بين متوسطي درجات المعلمات على مقياس إدارة الذات يعزى إلى نوع التعليم (خاص-حكومي). 3. لا يوجد فرق دال إحصائيا بين متوسطي درجات المعلمات على مقياس الكفاءة المهنية يعزى إلى نوع التعليم (خاص-حكومي). As a result of what the world has witnessed in recent years of cognitive development and enormous challenges that had the greatest impact on the educational process, and since the trend of educational competencies is one of the most prominent modern trends that prevailed in the programs of preparing teachers in general and kindergarten teachers in particular, and training them during the past three decades. Aims of the study: 1) Revealing the relationship between the average degrees of self-management and professional competence among kindergarten teachers. 2) Detecting the differences between the average scores of kindergarten teachers on the self-management scale, which is attributed to the type of education (private/ governmental. 3) Detecting the differences between the average scores of kindergarten teachers on the professional competence scale, which is attributed to the type of education (private/ government). Sample of the study: The study sample consisted of (110) kindergarten teachers who have a high qualification in the field of specialization "kindergarten", and practices of the profession in public, private, experimental and international schools. Methodology of the study: The researcher used the descriptive correlative approach due to the nature and objectives of the study. Tools of the study: Self-management scale prepared by/ Talaat Mansour, Ahmed El-Sayed Abdel-Moneim, Iman Muhammad Rayan Professional competence scale prepared by/ Nader Fathy Qassem, Abeer Saleh Abdullah Al-Haran. Rusults of the study: 1) There is a positive, statistically significant correlation between the scores of the research sample members on the self-management scale and their scores on the professional competence scale. 2) There is no statistically significant difference between the mean scores of the female teachers on the self-management scale due to the type of education (private-government). 3) There is no statistically significant difference between the mean scores of female teachers on the professional competence scale due to the type of education (private-government).
Keywords: المعلمات الروضة -- الرضا المهني -- الكفاءة الذاتية